13x-1=8x+39

Simple and best practice solution for 13x-1=8x+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-1=8x+39 equation:


Simplifying
13x + -1 = 8x + 39

Reorder the terms:
-1 + 13x = 8x + 39

Reorder the terms:
-1 + 13x = 39 + 8x

Solving
-1 + 13x = 39 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-1 + 13x + -8x = 39 + 8x + -8x

Combine like terms: 13x + -8x = 5x
-1 + 5x = 39 + 8x + -8x

Combine like terms: 8x + -8x = 0
-1 + 5x = 39 + 0
-1 + 5x = 39

Add '1' to each side of the equation.
-1 + 1 + 5x = 39 + 1

Combine like terms: -1 + 1 = 0
0 + 5x = 39 + 1
5x = 39 + 1

Combine like terms: 39 + 1 = 40
5x = 40

Divide each side by '5'.
x = 8

Simplifying
x = 8

See similar equations:

| n^2=-n | | 3*2-5+4*3-8+5*2= | | x-4+1=-3-x | | 3+3u=18 | | 250+150x=300y | | 10-3p+4p=20 | | F(4)=-3(-9)+10 | | 200+.25n=325 | | x+3x-2=18 | | 6m-2m= | | 9x+15=8x+4 | | 7=-5+4x | | (2x+50)=(5x+5) | | 56+x+85+42=180 | | 4x-5=102 | | 8-6(m-3)+4=4(m+7) | | 6x-1+11=53 | | x+-20=-16 | | F(3)=4(-5)-7 | | 9t^2-72t-54=0 | | (6x+5)(3x-4)=(2x+3)(9x-7) | | 3x-2y+5z=13 | | a^2+(a^2+4)=100 | | 3y-1+40=5x | | -6x+-18=-12 | | -(6n-4)=-7(2n+3)+3n | | 13x+7x=106 | | 3(X*5)=120 | | 13x+7s=106 | | x^2+20=8 | | 2x+2=92 | | 12/x=2/50 |

Equations solver categories